The Influence of Cybersecurity Disclosure, Tax Risk, Reputation and Auditor Experience on Audit Quality - Madani, Lutfi; Sofia, Alfira; Widarsono, Agus (Jurnal Pendidikan Akuntansi & Keuangan, 2024)
The aim of this research is to find out the influence of Cyber Security Disclosure, Tax Risk, Reputation and Auditor Experience on Audit Quality. The research method used is causal research, namely Multiple Regression Analysis. The findings from this research show that Cyber Security Disclosure has a positive effect on audit quality, tax risk has a positive effect on audit quality, auditor reputation has a positive effect on audit quality, and auditor experience has a negative effect on audit quality. It is hoped that these findings will provide useful information and can be applied in companies regarding the importance of disclosure of Cyber Security, Tax Risk, Reputation and Auditor Experience in determining audit quality. The novelty of this research is that it is the first research to link cyber security to audit quality.